2014
DOI: 10.1371/journal.pone.0087640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Markerless and Marker-Based Motion Capture Technologies through Simultaneous Data Collection during Gait: Proof of Concept

Abstract: During the last decade markerless motion capture techniques have gained an increasing interest in the biomechanics community. In the clinical field, however, the application of markerless techniques is still debated. This is mainly due to a limited number of papers dedicated to the comparison with the state of the art of marker based motion capture, in term of repeatability of the three dimensional joints' kinematics. In the present work the application of markerless technique to data acquired with a marker-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(102 citation statements)
references
References 24 publications
(74 reference statements)
2
95
1
4
Order By: Relevance
“…Specifically, Sandau et al [3] reported a RMSD of 2.6 deg for the hip, 3.5 deg for the knee, and 2.5 deg for the ankle, which are comparable with the RMSD values reported in Table 2 for the comfortable gait speed. Ceseracciu et al [4] reported a RMSD of 17.6 deg for the hip, 11.8 deg for the knee, and 7.2 deg for the ankle, sensibly higher than the values reported in this work. This further confirms the potential of the SEGMARK approach for the study of the lower limb motion in the sagittal plane for clinical applications.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Specifically, Sandau et al [3] reported a RMSD of 2.6 deg for the hip, 3.5 deg for the knee, and 2.5 deg for the ankle, which are comparable with the RMSD values reported in Table 2 for the comfortable gait speed. Ceseracciu et al [4] reported a RMSD of 17.6 deg for the hip, 11.8 deg for the knee, and 7.2 deg for the ankle, sensibly higher than the values reported in this work. This further confirms the potential of the SEGMARK approach for the study of the lower limb motion in the sagittal plane for clinical applications.…”
Section: Discussioncontrasting
confidence: 81%
“…However, in the abovementioned studies, the analyses were either limited to a single joint [20, 21], or they lacked a validation against a clinically accepted gold standard [22, 23]. These limitations hampered the wide spread use of such techniques in clinical settings [4, 7, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used techniques for recording human movement are marker-based and marker-less motion capture systems. Comparative analyses of different motion capture systems are given in references [5][6][7]. In order to record a 3D model of human motion, including the position and orientation of the required segments and joints, in this research we used an ART marker-based motion capture system.…”
Section: Introductionmentioning
confidence: 99%
“…Typically using markers attached to the patient’s body, such systems are accurate and deployed in many gait analysis laboratories [19], but are expensive, limited in range to the laboratory, and are limited to Line of Sight (LoS) conditions and to the markers’ locations. Existing marker-less video systems are less accurate, require multiple synchronized cameras [17], and sometimes still require an expert’s analysis of the resulting video streams [20]. …”
Section: Introductionmentioning
confidence: 99%